2013
DOI: 10.1177/2047487313487483e
|View full text |Cite
|
Sign up to set email alerts
|

Telemedical care: feasibility and perception of the patients and physicians: a survey-based acceptance analysis of the Telemedical Interventional Monitoring in Heart Failure (TIM-HF) trial

Abstract: RPM will be a medical care concept for recently hospitalized HF- patients in the near future but the optimal telemedical setting of RPM and the duration of this intervention have to be defined in further clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…24,25 Two telemedical centreslocated in two German regions -provided physicianled medical support for 24 h/day, seven days a week, according to defined standard operating procedures. Patients were enrolled from 165 practices in cardiology, internal medicine or general medicine, and were followed for at least 12 months with several outpatient visits.…”
Section: Early Detection Of Arrhythmiasmentioning
confidence: 99%
“…24,25 Two telemedical centreslocated in two German regions -provided physicianled medical support for 24 h/day, seven days a week, according to defined standard operating procedures. Patients were enrolled from 165 practices in cardiology, internal medicine or general medicine, and were followed for at least 12 months with several outpatient visits.…”
Section: Early Detection Of Arrhythmiasmentioning
confidence: 99%
“…Reports on patient compliance in monitoring programs are mixed. Patient adherence to the monitoring protocol was often good when only a small number of measurements with a small number of devices were required [9-11]. However, others reported poor compliance [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Gund et al indicated that the majority of the health care professionals queried in their study had a positive attitude towards current and future eHealth tools for out-of-hospital care for patients with chronic heart failure [22]. The Telemedical Interventional Monitoring in Heart Failure trial also indicated that eHealth acceptance among medical professionals was very high [23]. The authors also reported that it is necessary for implementation of online support systems to evaluate the acceptance among patients, but also among physicians who have a central role in disease treatment [23].…”
Section: Introductionmentioning
confidence: 99%
“…The Telemedical Interventional Monitoring in Heart Failure trial also indicated that eHealth acceptance among medical professionals was very high [23]. The authors also reported that it is necessary for implementation of online support systems to evaluate the acceptance among patients, but also among physicians who have a central role in disease treatment [23]. …”
Section: Introductionmentioning
confidence: 99%